The Effects of Resveratrol Supplementation on the Metabolism of Lipids in Metabolic Disorders - Ghavidel, Farideh; Hashemy, Seyed Isaac; Aliari, Mahdeyeh; Rajabian, Arezoo; Tabrizi, Masoud Homayouni; Atkin, Stephen L.; Jamialahmadi, Tannaz; Hosseini, Hossein; Sahebkar, Amirhossein (Current Medicinal Chemistry, 2025)
Lipids are stored energy sources in animals, and disturbance of lipid metabolism is associated with metabolic disorders, including cardiovascular diseases, obesity, nonalcoholic fatty liver disease, and diabetes. Modifying dysregulated lipid metabolism homeostasis can lead to enhanced therapeutic benefits, such as the use of statin therapy in cardiovascular disease. However, many natural compounds may have therapeutic utility to improve lipid metabolism. Resveratrol is a polyphenol extracted from dietary botanicals, including grapes and berries, which has been reported to affect many biological processes, including lipid metabolism. This review evaluates the effects of resveratrol on lipid metabolism dysregulation affecting atherosclerosis, diabetes, and nonalcoholic fatty liver disease (NAFLD). In addition, it details the mechanisms by which resveratrol may improve lipid metabolism homeostasis.
Keywords: resveratrol